IMPROVEMENT OF "BASIC SPELLING RULES OF THE UZBEK LANGUAGE" - Islomova Shahnoza (Web of Journals Publishing, 2024)
On August 24, 1995, the Cabinet of Ministers of the Republic of Uzbekistan adopted Resolution No. 339 "Confirmation of the basic spelling rules of the Uzbek language" Until 2023, this dictionary was published several times. The article discusses the differences, shortcomings, and conveniences of these prose.
Keywords: dictionary compiled by, spelling dictionary, printed, in words.